Jhon Ray - Alvarado Vázquez, Marco Antonio; Salcedo Martínez, Sergio Manuel (Universidad Autónoma de Nuevo León, 2024)
Breve resumen de la vida y obra del ilustre naturalista, botánico y zoólogo inglés Jhon Ray.